Design and performance test of kiln dry machine with intermitent drying method - Purwanto, Agung Ari; Widiyanto, Wahyu; Nurmadina; Wijayanto, Arip; Saputra, Deni (JTTM : Jurnal Terapan Teknik Mesin, 2026)
The quality of furniture products is largely determined by the quality of the wood raw materials, particularly the degree of dryness and moisture content of the wood. Wood drying can be done naturally with sunlight or using a drying machine. Most research on drying machine design is still conventional with a continuous drying method, namely controlling the external temperature and the wood surface to keep it stable. The research aims to produce a Kiln Dry machine that can support intermittent drying by setting and monitoring temperature and humidity controls. Drying with the intermittent method has been proven to reduce defects that occur in wood. The process flow in this research includes system design, system simulation, system creation, and testing the results. The designed drying machine is capable of operating intermittently or continuously, with an outer size of 90 cm × 100 cm × 100 cm and a drying room of 70 cm × 80 cm × 80 cm, the walls are designed using rock wool insulation to maintain the temperature of the machine room. The results of the function test show that the machine is capable of reaching a temperature of 196 °C in 60 minutes, with an operating temperature limited to 115 °C. The five-stage intermittent drying test with a ramp time of 10 minutes and a soak time of 10 minutes showed that the temperature control system was able to follow the set value at each stage, although there was a temperature overshoot of 2-5ºC at each stage in the Intermittent test